Pregnancy in a woman with a chronic descending thoracic aortic dissection. (June 2021) - Nair, Govind Krishna Kumar; Bhagra, Catriona; Sermer, Mathew; Silversides, Candice K; Pfaller, Birgit
Pregnancy increases aortic wall stress and, for a woman with a chronic dissection, this can lead to extension of the dissection, aortic rupture, and death. We report a pregnancy in a woman with a history of a chronic type B aortic dissection. As a child, she had repeat balloon dilation of aortic coarctation, and one of the procedures was complicated by an iatrogenic dissection at the dilation site. At the age of 27 years, she had a planned pregnancy.